Discipline and Organizational Culture Drive OTC Service Quality - Ilmi, Nur Fadilatul; Suwandi; Hapsari, Ira Maya (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Service quality in railway transport, especially in hygiene-based roles such as On Train Cleaning (OTC), is crucial to ensuring passenger comfort and satisfaction. Specific Background: PT KAI (Persero) Daop IV Semarang faces persistent challenges in maintaining cleaning standards, potentially rooted in internal workforce dynamics. Knowledge Gap: While prior studies have examined discipline, supervision, and organizational culture individually, their integrated impact on service quality within the railway cleaning context remains underexplored. Aims: This study aims to investigate the simultaneous influence of employee discipline, supervision, and organizational culture on the quality of OTC services. Results: Using a quantitative approach with 160 respondents and multiple linear regression, the study found that discipline (β = 0.234; p = 0.001) and organizational culture (β = 0.215; p = 0.013) significantly affect service quality, while supervision has no significant effect (β = 0.016; p = 0.839). The model explains 17.1% of service quality variance. Novelty: This research integrates three variables within a specialized operational setting—OTC in railway transport—rarely highlighted in previous studies. Implications: The findings suggest PT KAI should prioritize discipline and cultural reinforcement over supervisory interventions to elevate cleaning service standards and improve customer satisfaction.Highlight : Discipline and organizational culture contribute significantly to improving the quality of OTC services. Supervision does not have a significant influence, although it remains important to review. The study highlights the importance of internal factors in supporting train cleaning services. Keywords : Discipline, Supervision, Organizational Culture, Service Quality, OTC